INOVASI PEMBELAJARAN BAHASA INGGRIS MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA JURUSAN MATEMATIKA FMIPA UNIMED - Waminton Rajagukguk; Nice Rejoice Refisis (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2012)
Innovation of teaching to improved the student college’s achievement inthe teaching of Mathematic is explained. The research was aimed to investigate theeffectifity of various, innovated teaching models to improved the student’sachievement in various topic in Mathematic. The study was conduct experimentlyby using innovated teaching with “contextual” and “media”, which are thecompared with conventional teaching method. The result showed the innovation inthe teaching by using media and computer were found very effective and improvingthe ability of the student to understand the concept of mathematic. Studentachievement in the teaching of English Mathematic with the aid of Contextual(X=74,10) was found higher the teaching the same topic by using Conventionalmethod. (X=73,33), where the data analysis has shown that two methods aresignificantly differences. Students achievement with another innovated teachingmethod by using of media for the teaching distillation (X=81,33) was found higherthan that with conventional method, where the data analysis has shown that the twomethods were significantly difference.